Biodiversity of free-living marine nematodes in Banate Bay, Iloilo, Philippines - Sanchez, Kris Angeli S. (University of the Philippines Visayas, 2018)
Free-living marine nematodes (FLMN) are the most important components of the meiobenthic community as they are highly abundant and diverse, and have complex links to the microbial community and higher organisms. They are widely studied in temperate ecosystems, but there is a paucity of data in tropical areas. Meiobenthos samples and related environmental parameters were examined from six stations in Banate Bay, Iloilo, Philippines for three months in April (dry), July (onset of rain) and October (end of rainy season) in 2014. Marine nematodes constituted 90% of the total meiofauna and showed a mean density of 51.4±42.42 ind.cm-2. A total of 89 nematode genera from 23 families were identified, with Paracomedoma, Viscosia, Daptonema, Paramonohystera, and Cyatholaimus as the top five genera (35.6% of overall frequency). Spatial distribution of nematodes was variable/ nematode densities and genus richness (s) were relatively higher in the rainy season (Jul = 72.6 ind.cm-2 , s=60; Oct=56.8 ind.cm-2, s=77) than in dry summer (Apr=24.9 ind.cm-2, s=57). Three nematode assemblage were formed in the area with %organic matter (1.753), bottom turbidity (1.914) and temperature (-0.683) as the discriminant factors separating them. Density and species reichness were high during rainy season. High density was primarily influenced by low bottem salinity (β = -0.519), while high species richness was influenced by both low surface turbidity (β = -1.089) and low bottom salinity (β = -1.045). The nematode assemblage was dominated by epigrowth feeders (42%), with a shift to non-selective deposit feeders as sediment organic matter had accumulated in October. This study contributes to the scarce information on the taxonomy and ecology of free-living marine nematodes in tropical habitats and how their assemblages are affected by the monsoons and related environmental parameters.